Matriptase Expression and Zymogen Activation in Human Pilosebaceous Unit - Wu, Bai-Yao (SAGE Publications, 2014)
Studies of human genetic disorders and mouse models reveal the important roles of matriptase in hair growth. Here, we investigate matriptase expression and zymogen activation in hair follicles. We show: 1) layer-dependent distribution patterns, with much higher matriptase expression in cells of the outer root sheath and matrix cells of the hair bulb than in cells of the inner root sheath; 2) cycle-dependent expression patterns, with matriptase expressed in the anagen and catagen phases of the hair lifecycle, but not in the telogen phase; 3) reduced expression of the matriptase inhibitor, HAI-1, in the catagen phase, suggesting increased proteolytic activity in this phase; and 4) definitive matriptase zymogen activation patterns, with the highest matriptase activation observed in matrix cells and outer root sheath cells in the isthmus/bulge region. In sebaceous glands, matriptase is highly expressed in basal and ductal cells, with much lower expression in the differentiated, lipid-filled cells of the interior. We also show that matriptase potently activates hepatocyte growth factor (HGF) in vitro, and that the HGF receptor, c-Met, is co-expressed in those cells that express activated matriptase. Our observations suggest that the matriptase-HGF-c-MET pathway has the potential to be engaged, primarily in proliferative cells rather than terminally differentiated epithelial cells of the human pilosebaceous unit.